2008
DOI: 10.1007/s10311-008-0188-4
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and source apportionment of polycyclic aromatic hydrocarbons in the ambient air (Tehran, Iran)

Abstract: Polycyclic aromatic hydrocarbons (PAHs) are ubiquitous in the urban atmosphere and the atmospheric pollutants to be identified as the most suspected carcinogens. In early measurements of urban PAH concentrations in Tehran area, the correlation between concentrations of different species indicated that automobiles were the predominant source of emission of PAHs in this city. From the diagnostic ratios, the results indicated that PAHs in the ambient air in Tehran originate primarily from diesel and gasoline engi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(13 citation statements)
references
References 29 publications
1
11
1
Order By: Relevance
“…Khillare et al (2008) reported that B(b)F, in addition to B(ghi)P and Pyr, are indicators of diesel-driven vehicles which seem to correlate with the present observation that the bus stand, Venna lake and Panchgani having the highest vehicular activity have exceedingly higher concentration of these PAHs in comparison to the sites having low vehicular activity. Halek et al (2010) reported that diesel-driven vehicles are rich in acenaphthylene, acenaphthene and fluoranthrene which seems to be consistent with the present study as concentration of low molecular weight compounds are higher at all the sites in comparison to the control site.…”
Section: Polycyclic Aromatic Hydrocarbons In Lichenssupporting
confidence: 92%
See 1 more Smart Citation
“…Khillare et al (2008) reported that B(b)F, in addition to B(ghi)P and Pyr, are indicators of diesel-driven vehicles which seem to correlate with the present observation that the bus stand, Venna lake and Panchgani having the highest vehicular activity have exceedingly higher concentration of these PAHs in comparison to the sites having low vehicular activity. Halek et al (2010) reported that diesel-driven vehicles are rich in acenaphthylene, acenaphthene and fluoranthrene which seems to be consistent with the present study as concentration of low molecular weight compounds are higher at all the sites in comparison to the control site.…”
Section: Polycyclic Aromatic Hydrocarbons In Lichenssupporting
confidence: 92%
“…Chr) could be used to estimate the vehicular contribution to the air pollution which ranged between 0.5 (for diesel engine) and 0.75 (for gasoline engine) (Halek et al 2010). In the present study, the mean ratios of BaP/(BaP ?…”
Section: Polycyclic Aromatic Hydrocarbons In Lichensmentioning
confidence: 72%
“…Similar to Halek et al (2010), the presence of higher concentration of low molecular weight compounds, especially fluoranthene and acenaphthylene, indicates contribution of diesel vehicles to total PAHs load in the area, as the study area receives millions of tourists every month, which results in increased vehicular activity up to 800% during holy voyage (Joshi and Swami 2007).…”
Section: Resultsmentioning
confidence: 87%
“…It has been documented that PAH are often adhered to PM2.5 and PM10 in urban atmosphere (Stracquadanio et al 2007), and associated either with vehicle emissions in urban areas (Johnsen and Karlson 2007;Halek et al 2009) or coal (Liu et al 2009), tar or petroleum combustion (Johnsen and Karlson 2007). The concentration of PAH in ambient air very often reflects these pollution sources and the sink of PAH is very often the soil, sediment or surface waters; also, high concentration of PAH was found in the blackish deposits of roadsides (Jensen et al 2006).…”
Section: Discussionmentioning
confidence: 99%